Pv-Statcom Power Quality Enhancement with Shunt Active Power Filter - Shobhit Kureel, Dr. Shagufta Khan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Power consumption and energy demand are the major crises in the emerging world, leading to the increment in reliable resources. Reliability concerns were raised with the incorporation of solar energy sources employing typical electricity systems alignments. Furthermore, the fast-expanding use of electronically powered loads leads to problems of power quality in distribution networks. The significant power disturbances in the system occur due to the reactive power reduction, harmonic variation, and high voltage in distribution networks. An Active Power Filter is carried out to minimize the power quality disturbances in the distribution network to overcome the power quality defects. PV-STATCOM combined with the shunt Active Power Filter (APF) is the central part of the proposed work, which combines with the Unit Vector Template Method and Pulse Generator Techniques. In the distribution systems, PV-STATCOM, based on Voltage Source Converter, can inject and absorb the reactive and active power required in PCC to reduce power quality problems. The Low Voltage Ride analyses the performance of the PV-STATCOM system Through (LVRT) in an integrated grid system. The result analysis using MATLAB/SIMULINK shows that the proposed PV-STATCOM improved the performance rate in the power quality factor at the line of distribution systems. The Power outcomes of the proposed work changes from lagging power factor to unity Power factor with the changes in phase value of 26.7% to 5.0%, which lies with the IEEE standard limits.